2010
DOI: 10.3109/00207451003615755
|View full text |Cite
|
Sign up to set email alerts
|

Is Rhinorrhea an Under-Recognized Intrinsic Symptom of Parkinson Disease? A Prospective Pilot Study

Abstract: Rhinorrhea is more prevalent in PD patients compared to controls and it does not significantly impact performance on a smell test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have reported that rhinorrhea is more prevalent in patients with PD (24-50%) than in normal controls (6-26%) [2][3][4][5]. Furthermore, 38% of patients with PD with rhinorrhea reported worsening of rhinorrhea while eating [4].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have reported that rhinorrhea is more prevalent in patients with PD (24-50%) than in normal controls (6-26%) [2][3][4][5]. Furthermore, 38% of patients with PD with rhinorrhea reported worsening of rhinorrhea while eating [4].…”
Section: Discussionmentioning
confidence: 94%
“…However, the exact pathophysiology is still unclear [1]. Some reports suggest that rhinorrhea occurs more frequently among patients with Parkinson's disease (PD) than among healthy controls [2][3][4][5]. However, these reports are based on questionnaire surveys; detailed findings of rhinorrhea in patients with PD have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Patients with DLB have an increased risk of syncope/loss of consciousness, 1 which may be magnified among those with rhinorrhea. 4 Several studies have also substantiated a greater prevalence of rhinorrhea in patients with PD than in healthy controls (table), [2][3][4][5][6] with a range between 24% and 57%. Of interest, however, an association between rhinorrhea (a nondopaminergic feature 4 ) and anosmia (a dopaminergic one), a wellestablished premotor deficit in PD, was confirmed by only 1 6 of the 5 case-controlled studies examining such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, however, an association between rhinorrhea (a nondopaminergic feature 4 ) and anosmia (a dopaminergic one), a wellestablished premotor deficit in PD, was confirmed by only 1 6 of the 5 case-controlled studies examining such relationship. Further, rhinorrhea-affected patients with PD displayed no correlation with motor and nonmotor clinical variables in studies [4][5][6] that explored these parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation